COVID-19 Anxiety: Evidence of Hopelessness and Death Anxiety as Psychological Factors from a South Asian Nation - Bakul, Fariea; Nahar, Kamrun; Ahmed, Shahin (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
People with a fear of catching the coronavirus experienced unusually high levels of concern, leading to panic, death anxiety, hopelessness, social withdrawal, and various psychological problems. The present study aimed to investigate whether young people in Bangladesh suffer from death anxiety and hopelessness and whether these psychological factors correlate with the enhancement of coronavirus anxiety. Additionally, to assess the extent to which death anxiety and a sense of hopelessness can explain individual differences in coronavirus anxiety. A total of 592 young adults took part in the online survey, in which measures of coronavirus anxiety, death anxiety, and hopelessness were used. This study provides an in-depth understanding of the fear of contracting COVID-19 and coronavirus anxiety in individuals in terms of death anxiety and hopelessness. All three variables showed a significant positive correlation among them. The regression analysis identified psychological variables such as death anxiety and hopelessness as the most significant predictors of coronavirus anxiety in this study, accounting for 58.9% of the variability in coronavirus anxiety. Ultimately, this research is necessary to ensure that individuals, families, and communities are prepared to cope with the mental and physical health effects of a pandemic or a similar scenario in the future.